Hannevi'ah and Hannah : hearing women Biblical prophets in a woman's lyrical tradition - Lee, Nancy C. (James Clarke & Co, 2016)
Based on careful analysis of the lyrical traditions of ancient Hebrew, this challenging study reveals methods of discerning previously unnoticed female voices within Old Testament prophetic texts.